The Bad Citizen in Classical Athens - Christ, Matthew (Cambridge University Press, 2013)
The remarkable spread of democracy in the late-twentieth century has led to renewed interest in the roots of western democracy in ancient Athens. This study examines a facet of the Athenian experience that has received less scholarly attention than it deserves: the nature and scope of bad citizenship in classical Athens (508/7–322/1 B.C.) and the city’s responses, institutional and ideological, to this. Good citizenship is not ubiquitous in modern democracies, and it was not in democratic Athens